2020
DOI: 10.14366/usg.19035
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of torn supraspinatus tendons measured by shear wave elastography: a potential surrogate marker of chronicity?

Abstract: Purpose: This study investigated whether shear wave elastography (SWE) could be used to estimate the chronicity of supraspinatus tendon (SST) tears. Methods: A retrospective study was performed. From November 2015 to July 2016, 113 patients (52 men, 61 women; age range, 21 to 79 years) with persistent shoulder pain underwent 119 rotator cuff tendon examinations by routine B-mode ultrasonography, while SST elasticity was measured using SWE. Following the exclusion of eight suboptimal examinations, four examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Ultrasound imaging in particular supports the diagnosis of neuropathy by providing superior spatial resolution of small peripheral nerves and detailed information regarding lesion localization [6]. Moreover, as a recently-developed ultrasound imaging technology, shear-wave elastography (SWE) has the potential to provide quantitative values for the soft tissue stiffness of tissues, including the muscle [7], tendon [8], joint capsule [9], benign soft tissue mass [10], and nerves, and to improve the diagnostic performance of ultrasound imaging for various neuropathies involving the median, sciatic, tibial, and ulnar nerves [11][12][13][14][15]. The aim of this study was to verify whether cubital tunnel syndrome can be diagnosed based on quantitative ulnar nerve stiffness data obtained with SWE, as well as to compare patients with ulnar neuropathy to those with medial epicondylitis and lateral epicondylitis to establish a precise cut-off value of this parameter for use in ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging in particular supports the diagnosis of neuropathy by providing superior spatial resolution of small peripheral nerves and detailed information regarding lesion localization [6]. Moreover, as a recently-developed ultrasound imaging technology, shear-wave elastography (SWE) has the potential to provide quantitative values for the soft tissue stiffness of tissues, including the muscle [7], tendon [8], joint capsule [9], benign soft tissue mass [10], and nerves, and to improve the diagnostic performance of ultrasound imaging for various neuropathies involving the median, sciatic, tibial, and ulnar nerves [11][12][13][14][15]. The aim of this study was to verify whether cubital tunnel syndrome can be diagnosed based on quantitative ulnar nerve stiffness data obtained with SWE, as well as to compare patients with ulnar neuropathy to those with medial epicondylitis and lateral epicondylitis to establish a precise cut-off value of this parameter for use in ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis revealed that no significant difference in elastographically estimated tendon elasticity or strain ratio could be identified between shoulders with and without rotator cuff tendinopathy 17 . Similarly, no significant difference in elasticity values were found between normal and torn supraspinatous tendons, despite authors noting that elasticity differences were significant according to whether symptoms were one year in duration or less 18 . When strain ratios and functional scores were compared in patients with subacromial impingement syndrome, no significant correlation was found 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Elastography and its ability to predict physiologic tissue characteristics have been a source of ongoing interest in human tendinopathic imaging 17–19 . Previous authors have noted that imaging modalities’ diagnostic capability must be great enough to detect deformability differences between normal and diseased tissues 1,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed increased stiffness in LHBT in tendinosis conditions (1,2). In postsurgical status after supraspinatus tendon repair, SWE seems to show different short-term and long-term results concerning two newly published articles (8,11). In previously published papers, there are controversies for SE changes (hardness vs. softness) of supraspinatus tendinopathic conditions.…”
Section: Discussionmentioning
confidence: 98%